Mood of the Millennium. The National Millennium Exhibition of 1896 and Industrial Vocational Education - Vörös, Katalin (Autonomy and Responsibility Journal of Educational Sciences, 2022)
This paper investigates the (self)-representation of the Hungarian secondary vocational educational institutes related to the National Millennium Exhibition. Modernisation and nation-building aspirations simultaneously played a role in the educational purposes and the functioning of the specifi c institutes of the emerging modern Hungarian educational school system at the time of the Austro-Hungarian Monarchy. The fi n-de-siècle achievements and their distinctiveness appear to concentrate on the National Millennium Exhibition in the related texts. The current research is primarily based on contemporary reports and publications which describe Hungary in 1896 and the millennial celebration of the Settlement of Hungary. These sources are relevant to historical recognition in many ways. On the one hand, the examination of the texts contributes to the presentation of a certain type of education and the commemoration in light of Hungarian statehood, while, on the other hand, also pays recognition to the society and mentality of the period.